Self limiting fetal bradycardia associated with maternal evidence of dengue and chikungunya virus co-infection: a case report - Goel, Alka; Narain, Anupriya; Goel, Atul (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2019)
Dengue and chikungunya infections are commonly encountered by the clinicians in a tropical country like India. We report this case to emphasize the rare manifestations of self-limiting intrapartum bradycardia in fetuses of chikungunya and dengue infected mothers. A primigravida at 32 weeks of gestation presented with history of fever for one day. The blood investigations were positive for both dengue and chikungunya virus infection. On the third day of fever, NST showed a low baseline fetal heart rate of 95 to 100 beats per minute but good beat to beat variability and three accelerations in 10 minutes. This pattern persisted for 48 hours. Although, the finding initially appeared alarming, the change in baseline heart rate of fetus was transient and self-limiting and recovered completely. Hence, a judicious approach and close fetal surveillance can avoid hasty decisions regarding an early termination of pregnancy.